Formation mechanisms of deep and ultra-deep over pressure caprocks and their relationships with super-large gas fields in the petroliferous basins of China - Wei Li; Ziliang Yu; Xueke Wang; Zhichao Yu; Xuesong Lu; Qingfu Feng (Natural Gas Industry B, 2020)
Super-large natural gas fields have been discovered in the deep and ultra-deep layers of onshore and offshore petroliferous basins in China since the beginning of the 21st century, and the geological conditions for the formation of these gas fields and their development laws have already been discussed in a large number of literatures, but the relationship between over pressure and the formation of this kind of gas fields is still less researched. In this regard, this paper firstly analyzed the gas reservoir development law, sealing conditions and over pressure characteristics of deep and ultra-deep super-large gas fields. Then, the formation mechanisms of deep and ultra-deep over pressure caprocks were investigated and the development law of deep and ultra-deep super-large gas fields and their relationship with over pressure caprocks were discussed. Finally, the favorable areas for the next exploration of deep and ultra-deep natural gas were pointed out. And the following research results were obtained. First, the formation of deep and ultra-deep super-large gas fields is closely related to the development of over pressure caprocks. Over pressure caprock is a necessary condition for the formation of deep and ultra-deep super-large gas fields, and there are three over pressure formation mechanisms, including pressure seal of salt-gypsum layer, pressure seal of residual uplift and pressure seal of hydrocarbon-generating pressurization. Second, as for deep and ultra-deep over pressure caprocks and super-large gas fields, there are four reservoir–caprock assemblage modes under different pressure environments, i.e., over pressure salt-gypsum seal and over pressure super-large gas field (Type I), internal over pressure compartment and over pressure super-large gas field (Type II), high-pressure argillaceous shale seal at the bottom of over pressure compartment and normal-pressure super-larger gas field (Type III), and over pressure source rock seal and normal-pressure super-larger gas field (Type IV). In conclusion, there are Type I super-large gas fields in the Kuqa Depression of the Tarim Basin, types II and III in the Junggar Basin, types I–IV in the Sichuan Basin and Type IV in the Bohai Bay Basin.